2012
DOI: 10.1182/blood-2011-11-391383
|View full text |Cite
|
Sign up to set email alerts
|

Heparin in pregnant women with previous placenta-mediated pregnancy complications: a prospective, randomized, multicenter, controlled clinical trial

Abstract: To assess whether antithrombotic prophylaxis with low-molecular-weight heparin effectively prevents recurrence of late pregnancy complications, 135 women with previous history of preeclampsia, hemolytic anemia, elevated liver enzymes and low platelet count syndrome, intrauterine fetal death, fetal growth restriction, or placental abruption who had been referred within the 12th gestational week were randomized to medical surveillance alone (n ‫؍‬ 68

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 29 publications
3
105
2
7
Order By: Relevance
“…Some randomized controlled trials determined that LMWH is a preventive treatment for placenta mediated pregnancy complications [27,28]. However, Martinelli et al suggested that LMWH should not be routinely administered to prevent recurrence of placenta-mediated pregnancy complications [29]. Badawy et al did not detect The present study has several limitations.…”
Section: Discussioncontrasting
confidence: 46%
“…Some randomized controlled trials determined that LMWH is a preventive treatment for placenta mediated pregnancy complications [27,28]. However, Martinelli et al suggested that LMWH should not be routinely administered to prevent recurrence of placenta-mediated pregnancy complications [29]. Badawy et al did not detect The present study has several limitations.…”
Section: Discussioncontrasting
confidence: 46%
“…Only a small number of women with inherited thrombophilia were included in these studies (HA -BENOX study 24 women, SPIN study 10 women), with a nonsignificant increase in live birth rate in throm bophilic women treated with enoxiparin. Contrary to these findings, the two most recently published studies failed to demonstrate a beneficial effect of thromboprophylaxis on the pregnancy outcome in thrombophilic women with previous pregnancy complications other than recurrent miscarriages (61,62).…”
Section: Pregnancycontrasting
confidence: 39%
“…However, a recent trial, Heparin in Pregnant women with adverse Pregnancy outcome to improve the rate of successful pregnancy (HAPPY trial), failed to show any benefit of LMWH in preventing these adverse events, including pregnancy loss [23]. Subsequent studies have, however, shown that treatment with LMWH appeared beneficial in preventing the more severe forms of these adverse events in a subgroup of women with thrombophilia.…”
Section: Treatment Of Recurrent Miscarriage In Thrombophiliamentioning
confidence: 96%